TESTING THE STRENGTH OF THE OUTSTANDING OF THE FISHING LINE AT RICKY TANGKERANG LABUAI FISHING POOL, BUKIT RAYA DISTRICT, PEKANBARU - Alexander Manalu; Bustari Bustari; Jonny Zain (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
In this recent days, fishing activities have used various and varied fishing gear, one of them is fishing rods. Fishing gear has an important component, namely fishingline. Fishing line nowadays has many different brands, types and diameters to suit theneeds and desires of its users. However, the quality of fishing line is one of thedetermining factors for choosing a good fishing line. In determining the quality of fishingline breaking strength and elongation value can be used as benchmarks. This studyconducted trials on Shino Pro fishing line with diameters of 0.40mm and 0.35mm andTencara fishing line with 0.30mm diameter. Tests to measure the value of breakingstrength and elongation are carried out using a strength tester, the fishing line that used tobe tested is cut in to small size and clamped to the upper chuck and lower chuck whichhave been calibrated before to the initial position. The obtained value then used to input toT test until the results of breaking strength and elongation came out, the results shows thatthe 0.40mm Shino Pro fishing line has the best elongation value. Meanwhile, the resultsof the T test on the breaking strength value shows that Shino Pro 0.40mm fishing line hasbetter value than 0.35mm Shino Pro fishing line and the last is 0.30mm Tencara fishingline.